Blurring the lines : charter, public, private and religious schools coming together - Mulvey, Janet D.; Cooper, Bruce S.; Maloney, Arthur T. (Emerald Publishing Limited : Information Age Publishing, 2010)
This book, Blurring the Lines, has immediate appeal to policy-makers, and analysis in public and private sectors, as well as legal scholars and practitioners. It will be of interest, too, to university teachers working in the areas of "School Law," "School Policy and Politics," and "New Trends in American K-12 Education." The book treats the complex and interesting issues of Church-State and Public-Private education, the two great changing cross-road in US education.
Keywords: Public schools -- United States.; Charter schools -- United States.; Private schools -- United States.; Religion in the public schools -- United States.; Education and state -- United States.; Educational change -- United States.; School choice -- United States.; Education -- Teaching -- General.; Educational administration and organization.; Teaching skills and techniques.; elektronické knihy; electronic books